Gene Therapy for Cartilage and Bone Tissue Engineering - Hu, Yu-Chen (SpringerBriefs in Bioengineering, 2014)
"Gene Therapy for Cartilage and Bone Tissue Engineering" outlines the tissue engineering and possible applications of gene therapy in the field of biomedical engineering as well as basic principles of gene therapy, vectors and gene delivery, specifically for cartilage and bone engineering. It is intended for tissue engineers, cell therapists, regenerative medicine scientists and engineers, gene therapist and virologists. Dr. Yu-Chen Hu is a Distinguished Professor at the Department of Chemical Engineering, National Tsing Hua University and has received the Outstanding Research Award (National Science Council), Asia Research Award (Society of Chemical Engineers, Japan), and Professor Tsai-Teh Lai Award (Taiwan Institute of Chemical Engineers). He is also a fellow of the American Institute for Medical and Biological Engineering (AIMBE) and a member of the Tissue Engineering International & Regenerative Medicine Society (TERMIS)-Asia Pacific Council.